Poor oral health and hygiene habits in patients with infective endocarditis and previously identified predisposing cardiac condition: A prospective cohort study. Issue 5 (May 2022) - Moby, Vanessa; Millot, Sarah; Erpelding, Marie-Line; Euvrard, Edouard; Bourgeois, Geoffrey; Martin-Thomé, Hélène; Chirouze, Catherine; Tattevin, Pierre; Strady, Christophe; Agrinier, Nelly; Alla, Francois; Iung, Bernard; et al.
Highlights: Oral health and hygiene are suboptimal in patients with pre-identified risk of IE. 45% of the IE that developed in patients at risk of IE were due to oral pathogens. There is a clear need to improve oral health of patients at risk of IE. Graphical abstract: Image, graphical abstract